PENGARUH ZPT NABATI DAN MEDIA TUMBUH TERHADAP PEKEMBANGAN KOPI ROBUSTA - Setyo Andi Nugroho; Sonia Bagiatus; Ujang Setyoko; Titien Fatimah; Ika Lia Novenda; Pujiastuti Pujiastuti (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2022)
Indonesia occupies the 4th position of the 5 main coffee producing countries in the world. Coffee plants are a high foreign exchange earner in the Indonesian economy. Data from the Central Statistics Agency (BPS) show that Indonesia's coffee production in 2021 was the highest in the last decade, reaching 774.6 tonnes. This number increased by 2.75% from the previous year of 753.9 thousand tonnes. Coffee seed germination takes a long time due to seed dormancy. Coffee growth can be optimal with the provision of growth regulators. Good planting media can produce quality coffee seeds, because in good media there are nutrients needed by plants. The research was conducted at the Jember State Polytechnic Soil Wire House Laboratory in February-May 2022. Data were analyzed using Factorial RAK with a 5% BNJ follow-up test. The results showed that the combination treatment of planting media and natural ZPT concentrations had a significant effect on the generative growth of Robusta coffee (Coffea canephora L) including germination percentage, root length, height and seedling diameter.